Psychological determinants of leisure time physical activity participation among public university students in Malaysia - Lim, Khong Chiu; Kalsom Kayat, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The purpose of this study is to identify the influences of attitude, self-efficacy, and motivation on leisure time physical activity participation among undergraduate students at local public universities. The theory of planned behaviour and self-efficacy theory were used as a theoretical framework. The study sample comprised 1352 undergraduate students selected by random cluster sampling. Questionnaires were utilised to collect data. The results of the study showed that motivation and self-efficacy factors were the best predictors of leisure time physical activity participation. Furthermore, the results of path analysis revealed that the combination of attitude and self-efficacy had direct and indirect effects on motivation for leisure time physical activities participation among the students at local public universities. This study suggests that to encourage students’ leisure time physical activity participation and involvement, the university management should plan and organise programmes to develop positive attitudes among students and increase their self-efficacy and motivation levels for physical activity participation